2009
DOI: 10.1007/s10863-009-9227-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a non-specific permeability transition in mitochondria from Yarrowia lipolytica and Dipodascus (Endomyces) magnusii yeasts

Abstract: In this study we used tightly-coupled mitochondria from Yarrowia lipolytica and Dipodascus (Endomyces) magnusii yeasts, possessing a respiratory chain with the usual three points of energy conservation. High-amplitude swelling and collapse of the membrane potential were used as parameters for demonstrating induction of the mitochondrial permeability transition due to opening of a pore (mPTP). Mitochondria from Y. lipolytica, lacking a natural mitochondrial Ca(2+) uptake pathway, and from D. magnusii, harboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Mitochondria from Y. lipolytica cells were prepared as described previously (Kovaleva et al, 2009). They were fully active for at least 4 h when kept on ice.…”
Section: Isolated Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria from Y. lipolytica cells were prepared as described previously (Kovaleva et al, 2009). They were fully active for at least 4 h when kept on ice.…”
Section: Isolated Mitochondriamentioning
confidence: 99%
“…1S, see Supplement). Respiring mitochondria maintained their ΔΨ for a long time without any swelling (Kovaleva et al, 2009). Tightly-coupled yeast mitochondria have some advantages over animal mitochondria as they lack a Ca 2+ /P i -dependent pore (Kovaleva et al, 2009(Kovaleva et al, , 2010Trendeleva et al, 2011aTrendeleva et al, , 2011b, a fact facilitating interpretation of the data obtained.…”
Section: Uncoupling Effect Of с 12 Tpp In Yeast Mitochondriamentioning
confidence: 99%
“…Most classical studies of the PT were carried out in mitochondria obtained from mammals, although permeability changes, most notably those caused by ATP and substrates, have also been studied in yeast [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In recent years, the growing interest on the PT in cell death has prompted an increasing number of studies in mitochondria from other organisms including plants [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], fish [72,73], amphibians [74,75], and the brine shrimp Artemia franciscana, a salt-and anoxia-tolerant organism that may represent an exception in that it apparently lacks a PT [76].…”
Section: Introductionmentioning
confidence: 99%
“…Using Y. lipolytica and D. magnusii Kovaleva and coauthors (Kovaleva et al 2009) have showed that the mitochondrial Δψ decreases in the presence of the ionophore of ETH129 if Са 2+ (50-100 μМ) is applied at low concentrations. This effect was a bit slowed by P i and АТР application.…”
Section: Discussionmentioning
confidence: 99%